2007
DOI: 10.1007/s00167-007-0417-6
|View full text |Cite
|
Sign up to set email alerts
|

The attachments of the anteromedial and posterolateral fibre bundles of the anterior cruciate ligament

Abstract: The tibial attachments of the individual anteromedial (AM) and posterolateral (PL) fibre bundles and the entire attachment of the anterior cruciate ligament are described, relating them to consistent bony landmarks; 55 fresh-frozen specimens were measured. The fibre bundles were separated and excised at their attachments and their peripheries marked with a pen. Highresolution scaled digital photographs were taken of each dissected specimen and transferred onto a computer for analysis. A wide variation was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
111
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(128 citation statements)
references
References 24 publications
10
111
2
5
Order By: Relevance
“…Indeed, this review observed that the most consistent arthroscopic landmark for the tibial footprint was the anterior border of the posterior cruciate ligament, with the tibial footprint center 15 mm anterior to the border (Cuomo et al 2006; Edwards et al 2007; Heming et al 2007). However, it is worth noting that Hussein et al (Hwang et al 2012) performed a systematic review of subjective interpretations and failed to provide a definitive, quantitative synthesis through meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this review observed that the most consistent arthroscopic landmark for the tibial footprint was the anterior border of the posterior cruciate ligament, with the tibial footprint center 15 mm anterior to the border (Cuomo et al 2006; Edwards et al 2007; Heming et al 2007). However, it is worth noting that Hussein et al (Hwang et al 2012) performed a systematic review of subjective interpretations and failed to provide a definitive, quantitative synthesis through meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…First, the cartilage-based GPA provided a common geometric base across the specimens, effectively serving as a 3D geometric normalization procedure. In conventional morphometric studies, insertion site locations are expressed as percentages of the tibial plateau depth or width or similar representation and the normalization is therefore based on a single dimension [11], [15], [27], [28]. An underlying assumption for single-dimension-based normalization is that the involved morphometric measures adhere to isometric rather than allometric scaling [45].…”
Section: Discussionmentioning
confidence: 99%
“…A few observational studies have described the locations of the meniscal root attachments in relation to bony or soft tissue landmarks [31][33], but the location measures were not scaled or normalized by any tibial measure to elicit potential invariant or common morphological features. The shape variability of cruciate ligament insertions has been documented largely by qualitative descriptions [28], [29], [34], [35]. The ACL tibial insertion sites were found to be triangular or oval in most specimens in some studies [22], [36], and to be more variable than that of the femoral attachments in others [24], [28], [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the surgical intervention method used, the key element in ACL surgery remains knee and ACL anatomy, which have been resolved thoroughly for the tibial and femoral sides [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The ACL has two bundles, anteromedial and posterolateral, the names given from the tibial insertion site.…”
Section: Introductionmentioning
confidence: 99%